Preparation and characterisation of fly ash based geopolymer mortars - Temuujin, Jadambaa; van Riessen, Arie; MacKenzie, K. (Elsevier, 2010)
Geopolymer mortars with varying levels of sand aggregate were prepared and their physical andmechanical properties studied. The geopolymer binder to sand aggregate weight ratio was varied from9 to 1. Compressive strength and Young?s modulus of the fly ash based geopolymer paste were 60 MPaand 2.27 GPa and these values did not change significantly with addition of up to 50 wt.% sand aggregate. Geopolymer binder exhibited strong bonding to the sand aggregate. Increasing sand content without increasing the amount of alkaline activator resulted in a decreasing level of geopolymerisation within the binder system.